Non parametric mixture of strictly monotone regression models. Issue 2 (17th January 2018) - Zhang, Yi; Zheng, Qingle
ABSTRACT: In this article, we propose the non parametric mixture of strictly monotone regression models. For implementation, a two-step procedure is derived. We further establish the asymptotic normality of the resultant estimator and demonstrate its good performance through numerical examples.